Computer aided restoration of handwritten character strokes. (August 2017) - Sober, Barak; Levin, David
Abstract: This work suggests a new variational approach to the task of computer aided segmentation and restoration of incomplete characters, residing in a highly noisy document image. We model character strokes as the movement of a pen with a varying radius. Following this model, in order to fit the digital image, a cubic spline representation is being utilized to perform gradient descent steps, while maintaining interpolation at some initial (manually sampled) points. The proposed algorithm was used in the process of restoring approximately 1000 ancient Hebrew characters (dating to ca. 8th–7th century BCE), some of which are presented herein and show that the algorithm yields plausible results when applied on deteriorated documents. Highlights: Computer aided image segmentation for handwritten noisy documents. Combination of techniques pertaining to CAD and image processing. Gradient descent for B-Splines, which maintains interpolation at predefined points.